Corporate Governance and Dividend Policy in the Banking Sector on the Indonesian Stock Exchange - Mai, Muhamad Umar; Syarief, Mochamad Edman (University of Merdeka Malang, 2021)
This study is aimed at exploring the impact of corporate governance on dividend policy. The study was undertaken on the banking sector indexed in Indonesian Stock Exchange from 2009 to 2019. The method of data analysis used logistic regression and ordinary least squares regression. The findings demonstrated that four of five criteria of Corporate Governance had a major impact on dividend policy, such as propensity to pay dividends and dividend pay-out ratio. Institutional ownership, board of directors’ size and audit committee size have a positive influence on propensity to pay dividends while the female board of directors has a negative effect. This study did not show that independent board of commissioners had a substantial impact on the propensity to pay dividends and dividend pay-out ratio. The findings of this research contribute to the financial literature, in particular the relationship between corporate governance and dividend policy. These findings should be properly taken for consideration among investors when making decisions on their investments.DOI: https://doi.org/10.26905/jkdp.v25i1.4974